Evaluation of selected indicators of health care in the context of health care systems: Case of 27 European Union countries - Renata Halásková; Pavel Bednář (Scientific Papers of the University of Pardubice, Series D: Faculty of Economics and Administration, 2021)
Healthcare in European countries is provided through different systems run at national levels. The aim of the article is to evaluate selected health care indicators in EU countries, while accentuating similarities and differences between the EU countries in the context of health care systems. Applying the method of multivariate analysis, the selected health care indicators (from the areas of financing, service provision, health status) are evaluated on a set of 27 EU countries in the period 2013-2018. Factor analysis was applied to generate two factors (i.e. expenditures and satisfaction with health care, health status and bed availability in hospitals) from the original indicators of health care. As a next step, hierarchical cluster analysis was utilised to divide the EU countries into six clusters by similarity of the health care factors. The results of the factor analysis demonstrate marked differences between the countries regarding the evaluated health care factors. A higher (lower) level of socio-economic development is the aspect of better (worse) results of health care in the majority of the countries evaluated. However, according to the evaluated health care factors, clusters of similar countries used different systems of health care by type and source of financing. The findings thus demonstrate both similar and different approaches towards the provision of health care and funding health care systems in EU countries.
Keywords: C38; H51; I15; I18; 330; Health care; Health care financing; Health care indicators; Health care systems; Methods of multivariate analysis